Meno ; and, Phaedo - Plato (Cambridge texts in the history of philosophy, 2010)
"Plato's Meno and Phaedo are two of the most important works of ancient western philosophy and continue to be studied around the world. The Meno is a seminal work of epistemology. The Phaedo is a key source for Platonic metaphysics and for Plato's conception of the human soul. Together they illustrate the birth of Platonic philosophy from Plato's reflections on Socrates' life and doctrines. This edition offers new and accessible translations of both works, together with a thorough introduction that explains the arguments of the two dialogues and their place in Plato's thought"--